Measuring the ownership and control of UK listed firms: Some methodological challenges - Mira, Svetlana; Goergen, Marc (Academic Press, 2023)
While scholars in business,management,accounting and finance frequently use data on the ownership and control structure of companies in their research,we show that determining this structure for a UK public limited company using publicly available information can be fraught with a number of difficulties. The latest changes to the UK Listing rules following the Hill Review (2021) may further exacerbate these difficulties via the potential increase in listed companies with dual-class shares. With the help of case studies and further empirical work,we demonstrate some of the methodological challenges faced by researchers. We provide guidance on how to tackle these challenges. © 2023 The Authors
Keywords: Control; Corporate governance; Data; Methodology; Ownership; ODS 8 - Trabajo decente y crecimiento económico